On the Relations among CO2 Emissions, Gross Domestic Product, Energy Consumption, Electricity Use, Urbanization, and Income Inequality for a Sample of 134 Countries - Santillán-Salgado, Roberto J.; Valencia-Herrera, Humberto; Venegas-MartÃnez, Francisco (International Journal of Energy Economics and Policy, 2020)
This paper is aimed at examining the relations among CO2 emissions, gross domestic product (GDP) growth, energy consumption, electricity use, urbanization, and income inequality for a sample of 134 countries by using principal components analysis, Granger causality, vector error correction (VEC) models, and panel vector autoregression (PVAR) models. Data was obtained from the World Bank with annual observations from 1990 to 2014. The chosen countries are those with ten years or more of concurrent data of the variables under study. The main empirical findings suggest a Kuznets curve between CO2 emissions per capita and GDP per capita. In addition, CO2 emissions have a long-term relationship with economic growth, energy use, electricity use, urbanization, and inequality. Finally, in the short run, CO2 emissions depend on economic growth, urbanization, and income inequality. Key words: CO2 emissions, energy, economic growth, urbanization, Gini Index. JEL Classifications: F64, O13, O18, 044 DOI: https://doi.org/10.32479/ijeep.10070